Exercise training improves age-related changes in cerebral capillary vascularity through the upregulation of PI3K / Akt signaling - Chanpakdee, Channipa; Viboolvorakul, Sheepsumon; Patumraj, Suthiluk (Chulalongkorn Medical Journal, 2023)
Background: Currently, the number of the elderly has been rising sharply worldwide. Seemingly, age-induced cerebral endothelial dysfunction may lead to vascular abnormality that can later progress to cerebrovascular and neurodegenerative diseases. Moreover, several evidences have shown that age-related oxidative stress and decline in cellular function appeared in the vascular system both in humans and laboratory animals. The role of exercise training in the regulation of age-related oxidative stress and endothelial functions have been reported. Objectives: To investigate whether exercise training can prevent age-induced cerebral endothelial dysfunction associated to PI3K/Akt signaling. Methods: Male Wistar rats were randomly divided into 3 groups: sedentary-young group (SE-Young, 4 months), sedentary-aged group (SE-Aged, 22 - 24 months), and swimming trained-aged group (ET-Aged, 22 - 24 months), which individually swam 1 hour/day, 5 days/week for 8 weeks. After 8 weeks of the exercise period, the rats took rest for 24 hours. After a phosphate buffer saline (PBS) perfusion, brain was used for determining CD31 by immunohistochemistry. Vascular endothelial growth factor (VEGF), phospho-Akt level (p-Akt), and malondialdehyde (MDA) levels in the brain were measured by enzyme-linked immunosorbent assay. Results: The aged rats’ physiological characteristics had significant alteration when compared to the young group (P < 0.05). However, ET-Aged rats showed significantly reduced resting mean arterial blood pressure when compared to the young group (P < 0.05). This study also showed that exercise could upregulate VEGF, p-Akt level, and increase CD31 in the ET-aged group. Furthermore, tissue MDA in ET-Aged rats was significantly reduced when compared to SE-Aged rats (P < 0.05). Conclusion: Our findings imply that exercise training protected age-induced cerebral endothelial dysfunction associated with its effects of oxidative stress and PI3K/Akt signaling.